Hélio Serejo: por uma literatura entre as orilhas da fronteira - Anastacio, Elismar Bertoluci de Araujo [UNESP] (2014)
The current study aimed at investigating through Helio Serejo´s narratives (1912-2007), the way border is inserted and the way by which subjects who transit in the “abandoned border” in times of postwar and territorial occupation. In order to do so, the following plays were selected: Homens de aço: a luta nos ervais (2008), Vida de Erval (2008), Pelas Orilhas da Fronteira (2008), Caraí (2008), O Tereré que me inspira (2008), Pialando...no Más (2008), Carai Ervateiro (2008) and No Mundo Bruto dos Ervais (2008), due to the tales, stories and chronics, texts inserted into these plays shift particularly in the borders of Brazil-Paraguay and their real and fiction characters experience a sort of dispersive nomandism in an imaginary border zone, – in the forest – by the paths of Matte Laranjeira company (1877-1944). The possibility of analyzing through the spaces, from the crossing – continuous and by the time – the border subject may lead us to recognize possible identity representations with few studies. The investigation lies on the critical theoretical approach based on the cultural studies: Bhabha (2003), Hall (2003) Canclini (2003) e Achugar (2006), once the main themes transit by the relationship between literature and the identity formation aspects. We argue that serejian literary work is in narrating what was seen and listened, what happened and what would have happened in the memory and in the forgiven revival. Studying Hélio Serejo play is a way of (re)descovering aspects of “subjects´positioning” hidden by official history, particularly when the “border Brazil was once Paraguay” is concerned